Garden DIY Water Features - Maton, Chris (London Murdoch Books, 2002)
This work contains 20 innovative water features that combine exciting designs and unusual materials to create a varied range of projects for every type of garden.
Include Color Illustration and Index
Keywords: Ponds -- Water in landscape architecture -- Fountains